EVALUASI PEMBAGIAN RASKIN DI KABUPATEN BANTUL TAHUN 2007 DENGAN PENDEKATAN VULNERABILITY ANALYSIS AND MAPPING (VAM) - Karsinah, K (Semarang State University, 2010)
The goal of raskin program is to give the protection to the poor and vulnerability families by given the subsidized rice although they meet the nutrition need and reduce the poor families expenditure. Targeting the poor families eligible often not efficient. Bad targeting give the impact to the raskin program, some of program benefit leaked to non needy families. The research attempted to determine the area or region in Bantul the could be categorized into food vulnerability using VAM methods so they would be the targer of raskin program. The data used in the research were secondary data consist of classification and leveling family data in all area in Bantul in the year 2006 and raskin allocation data in Bantul in the year 2007. The finding of this research indicated that 17 areas observed, only 3 areas could be categorized in highest vulnerability, 7 areas categorized in high vulnerability, 2 areas categorized in medium vulnerability, 1 areas categorized in low vulnerability, 4 areas categorized in lowest vulnerability.